Trust the People? Populism, Trust, and Support for Direct Democracy - Wiesehomeier, Nina; Ruth Lovell, Saskia (Cogitatio Press, 2024)
Populism is commonly understood as a response to frustrations with the functioning of modern democracy, while the use of direct democratic mechanisms has been hailed as a remedy for the ailing of representative democracies. Indeed, populism’s emphasis on direct citizen participation in decision-making is tightly linked to its distrust of representative institutions and the political elite as the cornerstone of mediated representation. Trust, however, matters for any functioning democratic institutional arrangement, and we contend that its role warrants more attention when considering the viability of alternative modes of decision-making such as referendums, particularly in the nexus of populism–democracy. Using original public opinion surveys implemented in Argentina, Germany, Italy, Portugal, and Spain, we distinguish among different objects of trust—elites, institutions, “the people,” or the society at large. We also explore citizens’ levels of trust in these objects and their association with institutional designs of direct democracy. Our results offer preliminary insights into the importance of horizontal and vertical trust relationships in shaping procedural preferences for different configurations of direct democracy.
Keywords: Bottom‐up mechanisms; Direct democracy; Populism; Top‐down mechanisms; 59 Ciencia Política; ODS 10 - Reducción de las desigualdades; ODS 16 - Paz, justicia e instituciones sólidas